Optimization of transportation in a resort park - Tan, Xin Yi (2017)
Since the advancement of technology in the area of artificial intelligence over the years, engineers had started tapping on these resources to implement in the transportation sector. Selfdriving cars and autonomous vehicles (AV) are the outcome of the implementation of Artificial Intelligence resources in the field of transportation. In addition, with the deployment of autonomous vehicles on the ground by various countries, there is an increase in popularity and acceptance by the public to use AV as a tool to increase efficiency of the traffic. In Singapore, ST engineering (STE) had taken this initiative to test on a fleet of AVs to transport passengers from one location to another in Sentosa. In this project, PTV Vissim had been selected to model the network of Sentosa, the behaviour of the visitors and the routes of the existing public transport lines using real-time data to simulate realistic situations. Furthermore, to increase the relationship between visitors and the existing Sentosa public transportation, MATLAB had been selected as the programming language to program COM which acted as a “control centre” to manage the number of passengers waiting to travel from one area to another. With both the software and simulation platform in place, the next step would be to develop an on-demand algorithm to activate fleet of AVs/buses to meet the passengers’ needs during peak period to reduce waiting time.